The sustainability of rangeland to cropland nutrient transfer in semi-arid West Africa: ecological and social dimensions neglected in the debate - Turner, M. (International Livestock Centre for Africa, 1995)
The integration of crops and livestock has often been cited as a model for agricultural development in semi-arid West Africa. Recent formulations treat the adoption of more intensive forms of manuring as a critical step in agricultural development. These analyses have been criticised for ignoring or underestimating the possible negative consequences of such management on rangeland and livestock productivity. This paper critically examines this debate. It is argued that the agronomic benefits of manuring depend largely on nutrient transfers from non-cropped grazing lands. In this respect, the ecological critiques are correct in arguing that, except in sparsely cultivated areas, the livestock required to support continous cropping cannot be maintained by local pastures without external inputs. Over the long-term, such nutrient transfers cannot be sustained; nutrient outflows from pastures will exceed inflows resulting in a combination of reductions in livestock productivity, manure quality, pasture productivity and local livestock presence. However, these analyses have ignored the large influence of village-level agronomic and livestock management on the parameters used in such calculations. Once the temporal and spatial aspects of rangeland-cropland nutrient transfer are considered, it is shown that the dynamic sustainability of the process is determined, not simply by rangeland/cropland ratios and livestock stocking rates, but by differences in grazing and manure management at the village and household levels. Village-based livestock management is an area of active concern and experimentation by crop-livestock producers in semi-arid West Africa. More efficient nutrient management can be promoted through a combination of policy and extension efforts.